Adaptação ao campo universitário: trajetória escolar e herança familiar - Oliveira, Isabella Porto de (Universidade Federal de São Carlos, 2022)
The expansion of higher education accessibility due to law number 12.711/2012, which coded how students from public schools entered into the university, showed a necessity to ponder over how those students are adapting to university life. This brings up a question: which factors impact the adaptation process of students that originate from distinct social classes, that had inherited distinct capitals (economic, social, symbolic and cultural) and distinct school trajectories? In this way, the objective of this study is to understand how the process of adaptation of students from several social origins happens in the Federal University of São Carlos (UFSCar), looking to find the capitals and school trajectories that may possibly influence the initial phase of integration into the academic field. The theoric framework of this research is based upon Pierre Bourdieu contributions, which made an important critical analysis about the limits and contradictions of the french higher education democratization process and desmitifies the pedagogic optimism in which the students performance is related to just a few meritocratic questions. For this, online questionnaires and semi-structured interviews with the students from the most and least selective courses from each of the three science centers that are present in the São Carlos UFSCar campus were used, as well as a documental analisis and bibliographic survey to find out which were those courses. In trying to identify the possible profitable scholar capitals in the trajectory of the students, we understand that the access to the cultural capital where much higher in the courses with more selectivity, and brought more advantage to their adaptation process to the university field. The family heritage of an informational and cultural capital helped the first group of students to have less difficulties in the amount of reading and study required in their courses, since even before entering into the university they were encouraged to have a reading habit and they read more books per year. As such, the economic and cultural capitals favor the adaptation of those students into the university-academic field. The data about the origin and social standing, the difficulties that were found by the students, the possible influence of family heritage and the school trajectories point to a need to consider those informations when trying to understand how the adaptation process of students to the university field happens. The strategic investments made by the families during the school trajectory also may influence this process. so we consider that the difficulties presented by the students about their adaptation process may be related to the cultural capital and habitus that comes with their social standing and family heritage. Distinct trajectories may imply greater difficulties for some students and to understand this question may desmitify the gift ideology.
Adaptation to the university field: school trajectory and family heritage
Keywords: Trajetórias; Herança familiar; Capital cultural; Ensino Superior; university adaptation; trajectories; family heritage; cultural capital; higher education; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO